Impact of single-nucleotide variants and individual characteristics on adverse events of L-asparaginase in children with acute lymphoblastic leukemia - Gándara-Mireles, Jesús Alonso; Lares-Asseff, Ismael; Reyes Espinoza, Elio Aarón; Loera Castañeda, Verónica; Córdova Hurtado, Lourdes Patricia; Reyes Gutiérrez, Flor de María; Sandoval-Cabrera, Antonio; Villanueva Fierro, Ignacio; Grijalva Ávila, Julio Cesar; Castro Arreola, Claudia; Patrón-Romero, Leslie; Almanza Reyes, Horacio (Frontiers in Pharmacology, 2024)
L-Asparaginase (L-Asp) is a key drug in the treatment of acute lymphoblastic leukemia (ALL); however, it is commonly associated with the occurrence of adverse events (AE). Risk factors such as age, sex, nutritional status, and some single nucleotide variants (SNVs) in specific genes could be related to hypersensitivity reactions to L-Asp. The objective of this study was to identify the influence of individual characteristics and three SNVs in the GRIA1 and NFATC2 genes on the occurrence of the most significant adverse events caused by the use of L-Asp in Mexican children with ALL. Eightyfive children from ages 0 to 17 years old diagnosed with ALL were included. The patients were treated at two hospital centers in Mexico. The SNV genotypes of the GRI1A and NFATC2 genes studied were examined using real-time qPCR. The evaluation of AE was carried out according to the Common Terminology Criteria for adverse events, and the determination of anti-L-Asp antibodies was conducted using Western blot immunoassay. Homozygosity (AA) of the GRIA1 rs4958351 SNV was significantly associated with the occurrence of AE with the use of L-Asp (OR= 4.05; CI 95%= 1.06 to 15.40, p=0.04) and was strongly associated with the development of anti-L-Asp antibodies (OR=3.4375, CI 95%= 1.04 to 11.25, p=0.04). With this, we found a significant risk association for the SNV rs4958351 of the GRIA1 gene. On the other hand, we did not find significant risk associations 2 for the GRIA1 rs6889909 and NFATC2 rs6021191 SNVs, although other populations have shown a significant risk. Our study has some limitations, such as the small sample size, the heterogeneity in adverse events due to the patients' different regions of origin, and the limited ability to conduct a more detailed follow-up on pancreatitis. Additionally, since no significant associations were found between the NFATC2 rs6021191 and GRIA1 rs6889909 SNVs and the development of adverse events or the presence of antibodies due to the use of L-Asp, it is necessary to investigate new specific SNVs that may improve the efficacy and safety of treatment in Mexican children with ALL.